Ulcer Traumaticus et Causa Trauma Occlusion - Amalia Eka Setya Dewi; Atia Nurul Sidiqa (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: A Traumatic Ulcer is a type of ulcer that is caused by local factors. Traumatic ulcers usually occur on the soft tissues in the oral cavity and can be caused by many factors, one of which is occlusion trauma. Case:  The clinical picture of an ulcer is that of an ulcer on the oral mucosa in an acute inflammatory state, including varying degrees of pain, redness, and swelling in various sizes and shapes. The initial lesion in traumatic ulcers is usually felt by people in the form of annoying pain. Case Management: Medication therapy such as Aloclair gel containing olyvinylpyrrolidone (PVP) which has mucoprotective activity works by forming a layer over the ulcer that will protect the affected nerve endings so as to prevent irritation and reduce pain in the ulcer. Hyaluronic acid and Aloevera support the natural healing process of damaged tissue. Discussion: A traumatic ulcer lesion can heal on its own within 10 to 14 days if the irritant or cause is removed because during this time there will be a process of keratinization and renewal of oral mucosal epithelial cells. Conclusion:Traumatic ulcers can heal within a few weeks by addressing the causative factors, administering medication, and encouraging patients to maintain good nutrition and oral health.